Beyond the body? The Future of Embodied Cognition - Guy Dove (Frontiers Research Topics, 2016)
Embodied cognition represents one of most important research programs in contemporary cognitive science. Although there is a diversity of opinion concerning the nature of embodiment, the core idea is that cognitive processes are influenced by body morphology, emotions, and sensorimotor systems. This idea is supported by an ever increasing collection of empirical studies that fall into two broad classes: one consisting of experiments that implicate action, emotion, and perception systems in seemingly abstract cognitive tasks and the other consisting of experiments that demonstrate the contribution of bodily interaction with the external environment to the performance of such tasks. Now that the research program of embodied cognition is well established, the time seems right for assessing its further promise and potential limitations. This research topic aims to create an interdisciplinary forum for discussing where we go from here. Given that we have good reason to think that the body influences cognition in surprisingly robust ways, the central question is no longer whether or not any cognitive processes are embodied. Instead, other questions have come to the fore: To what extent are cognitive processes in general embodied? Are there disembodied processes? Among those that are embodied, how are they embodied? Is there more than one kind of embodiment? Is embodiment a matter of degree? There are a number of specific issues that could be addressed by submissions to this research topic. Some supporters of embodied cognition eschew representations. Should anti-representationalism be a core part of an embodied approach? What role should dynamical models play? Research in embodied cognition has tended to focus on the importance of sensorimotor areas for cognition. What are the functions of multimodal or amodal brain areas? Abstract concepts have proved to be a challenge for embodied cognition. How should they be handled? Should researchers allow for some form of weak embodiment? Currently, there is a split between those who offer a simulation-based approach to embodiment and those who offer an enactive approach. Who is right? Should there be a rapprochement between these two groups? Some experimental and robotics researchers have recently shown a great deal of interest in the idea that external resources such as language can serve as form of cognitive scaffolding. What are the implications of this idea for embodied cognition? This research topic aims to bring together empirical and theoretical work from a diversity of perspectives. Submissions are sought from any of the major disciplines associated with cognitive science, including but not necessarily limited to anthropology, cognitive psychology, computational modeling, linguistics, neuroscience, philosophy, robotics, and social psychology. Researchers are encouraged to submit papers discussing experiments, methods, models, or theories that speak to the issue of the future of embodied cognition.